Strongly Anisotropic Strain‐Tunability of Excitons in Exfoliated ZrSe3. Issue 1 (15th October 2021) - Li, Hao; Sanchez‐Santolino, Gabriel; Puebla, Sergio; Frisenda, Riccardo; Al‐Enizi, Abdullah M.; Nafady, Ayman; D'Agosta, Roberto; Castellanos‐Gomez, Andres
Abstract: The effect of uniaxial strain on the band structure of ZrSe3, a semiconducting material with a marked in‐plane structural anisotropy, is studied. By using a modified three‐point bending test apparatus, thin ZrSe3 flakes are subjected to uniaxial strain along different crystalline orientations monitoring the effect of strain on their optical properties through micro‐reflectance spectroscopy. The obtained spectra show excitonic features that blueshift upon uniaxial tension. This shift is strongly dependent on the direction along which the strain is being applied. When the flakes are strained along the b ‐axis, the exciton peak shifts at ≈60–95 meV % −1, while along the a ‐axis, the shift only reaches ≈0–15 meV % −1 . Ab initio calculations are conducted to study the influence of uniaxial strain, applied along different crystal directions, on the band structure and reflectance spectra of ZrSe3, exhibiting a remarkable agreement with the experimental results. Abstract : Zirconium triselenide is a 2D semiconductor material with an interesting in‐plane anisotropic crystal structure. Here, it is demonstrated that the excitons of this material are very sensitive to uniaxial strains and, interestingly, their tunability strongly depends on the direction along which the uniaxial strain is applied.